Probing experience : from assessment of user emotions and behaviour to development of products - Westerink, Joyce H. D. M. (Springer, 2017)
This book adheres to the vision that in the future compelling user experiences will be key differentiating benefits of products and services. Evaluating the user experience plays a central role, not only during the design process, but also during regular usage: for instance a video recorder that recommends TV programs that fit your current mood, a product that measures your current level of relaxation and produces advice on how to balance your life, or a module that alerts a factory operator when he is getting drowsy. Such systems are required to assess and interpret user experiences (almost).